2022
DOI: 10.1021/acsomega.2c06660
|View full text |Cite
|
Sign up to set email alerts
|

Isocoumarins and Benzoquinones with Their Proprotein Convertase Subtilisin/Kexin Type 9 Expression Inhibitory Activities from Dried Roots of Lysimachia vulgaris

Abstract: A phytochemical investigation of the n-hexane-soluble chemical constituents of Lysimachia vulgaris roots allowed for selection using a proprotein convertase subtilisin-kexin type 9 (PCSK9) mRNA expression monitoring assay in HepG2 cells. This led to the isolation of two previously undescribed isocoumarins of natural origin, 8′Z,11′Z-octadecadienyl-6,8-dihydroxyisocoumarin (1) and 3-pentadecyl-6,8-dihydroxyisocoumarin (2), along with 20 previously reported compounds (3−22). All of the structures were establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The carotenoid compound asthaxanthin [110] and the Chinese herbal preparation Bai He Gu Jin Tiang, which contains ten distinct herbs [111], have both been identified as acting on AKR1C2 in silico, which may be associated with anti-depressant and anti-obesity effects. Phytochemicals derived from Lysimachia vulgaris, Protium heptaphyllum and Salvia plebeia have been shown to reduce PCSK9 expression in vitro, though these have been investigated as lipid-lowering agents and not specifically for obesity or depression [112][113][114]. Finally, certain plant products, such as rottlerin [115], Coriandrum sativum metabolites [116], and the ginseng derivative gintonin [117], have been shown to be pharmacologically active at the KCNE1 binding site; however, these properties have been evaluated in the context of anti-arrhythmic or anti-convulsant activities.…”
Section: Natural Compoundsmentioning
confidence: 99%
“…The carotenoid compound asthaxanthin [110] and the Chinese herbal preparation Bai He Gu Jin Tiang, which contains ten distinct herbs [111], have both been identified as acting on AKR1C2 in silico, which may be associated with anti-depressant and anti-obesity effects. Phytochemicals derived from Lysimachia vulgaris, Protium heptaphyllum and Salvia plebeia have been shown to reduce PCSK9 expression in vitro, though these have been investigated as lipid-lowering agents and not specifically for obesity or depression [112][113][114]. Finally, certain plant products, such as rottlerin [115], Coriandrum sativum metabolites [116], and the ginseng derivative gintonin [117], have been shown to be pharmacologically active at the KCNE1 binding site; however, these properties have been evaluated in the context of anti-arrhythmic or anti-convulsant activities.…”
Section: Natural Compoundsmentioning
confidence: 99%
“…9 Inducible degrader of LDL receptor (IDOL) has also emerged as a LDLR degrader due to its function as E3 ubiquitin ligase, and this is how PCSK9 and IDOL have become major drug targets for CVD by minimizing LDL-C. 8–10 To date, two antibody drugs (alirocumab and evolocumab) and one siRNA drug (inclisiran) have been approved for clinical practice as PCSK9 inhibitors, 11 whereas synthetic or natural product-derived small molecules are yet to be released to the market. Many efforts to discover natural product-derived compounds with a modulatory effect on PCSK9 or IDOL have been made, and various structures including alkaloid, 12 diterpene, 13 flavonoid, 14 isocoumarin, 15 lignan, 16 saponin, 17 and stilbene 18 have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was reported that Betulin could not cross blood‒brain barrier, limiting its clinical translation potential. 4 Recently, novel inhibitors (PCSK9-IN-9 and 5-O-methylembelin) have been reported to inhibit the mRNA level of SREBP-2 but not SREBP-1 5 (summarized in Table 1 ). Therefore, it is crucial to conduct further investigations on specific SREBP-2 inhibition, and the development of therapeutic targeting this druggable target.…”
mentioning
confidence: 99%